(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Limnology is the study of inland water bodies particularly rivers, ponds and lakes, including their biological, physical, chemical and hydrobiological aspects. From the time of Forel (1841-1912), who is known as founder and Father of limnology, the biogenic material balance of natural waters was observed and recorded. The pioneer investigations of Forel (1901) were focused on Le Leman (Lake Geneva) where he exposed the preliminary facts concerning the fauna of freshwater. Then limnology was studied with reference to organisms, especially plankton (Welch, 1952). The discovery of plankton by Victor Hansen in 1887 and Fritsch in 1907 was an outstanding event in the field of limnology. In India,the First limnological investigation done by Prasad on the seasonal variation of pond organisms (V.P.Singh, 1960).